Business, Government and Economic Institutions in China (International Political Economy Series,, 2018)
This book brings together conceptual and empirical analyses of the causes and consequences of changing business-government relations in China since the 1990s, against the backdrop of the country's increased integration with the global political economy. More specifically, it provides an interdisciplinary account of how the dominant patterns of interactions between state actors, firms and business organizations have changed across regions and industries, and how the changing varieties of these patterns have interacted with the evolution of key market institutions in China. The contributors to this edited volume posit that business-government relations comprise a key linchpin that defines the Chinese political economy and calibrates the character of its constitutive institutional arrangements. .